2021
DOI: 10.1681/asn.2020081215
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Complexity of Death-Censored Kidney Allograft Failure

Abstract: BackgroundFew studies have thoroughly investigated the causes of kidney graft loss (GL), despite its importance.MethodsA novel approach assigns each persistent and relevant decline in renal function over the lifetime of a renal allograft to a standardized category, hypothesizing that singular or multiple events finally lead to GL. An adjudication committee of three physicians retrospectively evaluated indication biopsies, laboratory testing, and medical history of all 303 GLs among all 1642 recipients of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 29 publications
(42 reference statements)
0
100
0
2
Order By: Relevance
“…dnDSA formation at post-transplantation is the leading cause of developing chronic antibody-mediated (cABMR) rejection (8,9); they have a particularly worse impact upon kidney allograft survival especially when they bind complement, i.e., either C1q (9,10) or C3d (11) components. Recently, Mayrdorfer et al have reassessed the causes of kidney allograft failure in the modern immunosuppression era in a prospective cohort of 1,642 kidney transplant (KTx) recipients (12). They found that in 51.2% of patients with allograft failure, more than one cause was involved.…”
Section: Introductionmentioning
confidence: 99%
“…dnDSA formation at post-transplantation is the leading cause of developing chronic antibody-mediated (cABMR) rejection (8,9); they have a particularly worse impact upon kidney allograft survival especially when they bind complement, i.e., either C1q (9,10) or C3d (11) components. Recently, Mayrdorfer et al have reassessed the causes of kidney allograft failure in the modern immunosuppression era in a prospective cohort of 1,642 kidney transplant (KTx) recipients (12). They found that in 51.2% of patients with allograft failure, more than one cause was involved.…”
Section: Introductionmentioning
confidence: 99%
“…Mayrdorfer et al found that alloimmunity accounted for 64.7% of graft losses (T cell–mediated rejection in 34% and AMR in 30.7%). 8 Medical causes accounted for only 36.3%. Chand et al found that 42.3% of their 97 cases of GF beyond 1 mo were due to alloimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Late TCMR has been suggested as a predictor of low GS in previous studies [27,28]. Recently, Mayrdorfer et al suggested that TCMR might be a contributing factor in about one-third of early and late graft failures [29]. For over a long term after transplantation, nonimmunologic factors, including chronic toxicity, had great importance in graft function [30].…”
Section: Plos Onementioning
confidence: 99%